Synergistic Effect To Two Type Of Lactic Acid Bacteria And Their Synbiotic Effect With Prebiotic Raisin Against Some Pathogenic Bacteria (Journal of the College of Basic Education, 2022)
The present study demonstrated the potential of using raisins as prebiotic a result of antibacterial activity shown by the aqueous extract of raisins against different types of bacteria . Also this study conducted on two types of probiotic to know the synergistic effect to both of them together. Synbiotic (prebiotic and probiotic) also tested against test bacteria. Results revealed that the highest activity in synbiotic & synergistic effect against E.coli and Listeria the zones of inhibition showed the range of (24-25) mm for this effect., While staphylococcus aureus only could resist this synergistic effect. Prebiotic had the lower activity compared with others, so we conclude that the synbiotic effect is the better against all pathogenic bacteria in the study.